Anger and impulsiveness in migraine patients with and without aura. (3rd March 2020) - Tanik, Nermin; Akturk, Tülin; Saçmaci, Hikmet; Inan, Levent Ertugrul
ABSTRACT: Background and purpose : Migraine is a common primary headache disorder triggered by internal or external stimuli. Impulsitivity and anger are associated with many neurological and psychiatric disorders. The aim of this study was to investigate the anger and impulsivity in migraine patients with or without aura. Methods : A total of 55 patients aged between 18 and 55, who were diagnosed with episodic migraine (31 with aura and 24 without aura) and 40 healthy controls were enrolled in this prospective cross-sectional study. Migraine diagnosis and classification were based on criteria from the International Classification of Headache Disorders, 3rd edition (beta version). Multidimensional Anger Scale and Barratt Impulsivity Scale-11 were administered to the patient and control groups. Results :Migraine patients with aura, migraine patients without aura and control groups were compared, anger symptoms were significantly higher in migraine patients with aura (p < 0.001), but between these groups there was no significant difference in terms of impulsivity (p = 0.711). Conclusions : It was found that anger symptoms were more common in migraine patients with aura compared to migraine patients without aura and control group, but in impulsitivity there was no difference between groups. Further studies in future investigating the relation between migraine with aura and anger may pave the way for different and more specified treatment approach.